2014
DOI: 10.5194/tc-8-521-2014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling bulk density and snow water equivalent using daily snow depth observations

Abstract: Abstract. Bulk density is a fundamental property of snow relating its depth and mass. Previously, two simple models of bulk density (depending on snow depth, date, and location) have been developed to convert snow depth observations to snow water equivalent (SWE) estimates. However, these models were not intended for application at the daily time step. We develop a new model of bulk density for the daily time step and demonstrate its improved skill over the existing models.Snow depth and density are negatively… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 28 publications
3
48
1
Order By: Relevance
“…Elder et al (1998), Anderton et al (2004) and Anderson et al (2014) found the variability of spring snow density to be insignificantly correlated with elevation in their studies, while Zhong et al (2014) found negative correlations with elevation in a meta-study of densities in the former USSR. A range of results has also been reported for the snow-density correlation with depth showing both positive and negative correlations depending on the age of the snow and season (Arons and Colbeck, 1995;McCreight and Small, 2014).…”
Section: Snow Densitymentioning
confidence: 78%
“…Elder et al (1998), Anderton et al (2004) and Anderson et al (2014) found the variability of spring snow density to be insignificantly correlated with elevation in their studies, while Zhong et al (2014) found negative correlations with elevation in a meta-study of densities in the former USSR. A range of results has also been reported for the snow-density correlation with depth showing both positive and negative correlations depending on the age of the snow and season (Arons and Colbeck, 1995;McCreight and Small, 2014).…”
Section: Snow Densitymentioning
confidence: 78%
“…Compared with snow density, snow depth shows much larger temporal variability (Sturm et al, 2010), which makes it difficult to assign temporally varying uncertainty levels for the snow depth estimates. However, the above scheme partially accounts for uncertainties in the snow depth data due to a positive correlation between snow depth and density at longer timescales (McCreight and Small, 2014). For both model baseline simulations and sensitivity runs, the model was spunup for 50 years to bring the top 10 m soil temperature profile into dynamic equilibrium with model inputs for the year 2000, followed by a transit run from 2001 to 2015.…”
Section: Model Sensitivity Analysismentioning
confidence: 99%
“…There are many such methods available to predict snow density in this way, from empirical models that estimate density range in complexity from linear regressions (e.g., Elder et al 1991;Marchand and Killingtveit 2004;Lundberg et al 2006;Jonas et al 2009) to the inclusion of multiple predictor variables (e.g., SD, day of year, elevation) and lookup tables (e.g., Jonas et al 2009;Sturm et al 2010;McCreight and Small 2014). Avanzi et al (2015a) compared 18 empirical density models to 10 SNOTEL observations and found a general overestimation of density and an increase in error with increasing elevation.…”
Section: Introductionmentioning
confidence: 99%